Leveraging Digital Technologies for Urban Resilience: Addressing Economic, Social, and Environmental Challenges in Developing Country Cities - Jose Antonio Dela Cruz (Techne: Journal of Engineering, Technology and Industrial Applications, 2025)
This study aims to explore urban resilience strategies in developing countries in addressing social, economic, and environmental challenges, especially in rapidly urbanizing cities such as Dhaka, Nairobi, Mumbai, and Manila. The study analyzes secondary data from government reports, international agencies such as UN-Habitat and the World Bank, and academic literature to evaluate the effectiveness of green infrastructure, adaptive technologies, and local-based policies in enhancing urban resilience using a case study approach. The results show that local-based policies that take into account the social, economic, and environmental characteristics of each city are more effective than generic approaches. Green infrastructure, such as mangrove parks and water channels, and simple technologies, such as early warning systems, have been shown to have significant impacts in enhancing resilience to climate change and natural disasters. In addition, collaboration with international agencies plays an important role in providing technical and financial support to cities with limited resources.